If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4n + -12 = -20 Reorder the terms: -12 + -4n = -20 Solving -12 + -4n = -20 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -4n = -20 + 12 Combine like terms: -12 + 12 = 0 0 + -4n = -20 + 12 -4n = -20 + 12 Combine like terms: -20 + 12 = -8 -4n = -8 Divide each side by '-4'. n = 2 Simplifying n = 2
| 5x+3=4x-9 | | 3(y+3)+y=2(y+5)-4 | | -9(-3x-5)-6x=-6x | | 3x-8=8x+7 | | -3p-8=19 | | 3t+8(2t-6)=2+ | | 12=-z/4+3 | | 3z^2-34x-24=0 | | 8*0-5y=80 | | 5-5p=45 | | -4(5x-5)=-16x-9 | | (3x+5)(2x+5)=0 | | -9x=-10x+7 | | -3(t-1)+9t=4t-7 | | -x/10+13=-3 | | 13-8x=93-36x | | 4-3x=24 | | 5-2x-3=-4 | | 2x+12=3-7x | | 4n+3=-17 | | 3p=-9p | | 6=5x-9 | | 5x*2+6x+1= | | 8x+43=11 | | 7x+2=4x+20 | | y=-2+8*0 | | Y=3mx+5b | | 6d^2+16d+8=0 | | -42-2=14-9x | | 4x-1=-5x-19 | | -42-2x=14-9 | | 6x=-7x+13 |